Uji toksisitas menggunakan metode BSLT dan uji antibakteri Staphylococcus aureus dan Escherichia coli ekstrak dan fraksi daun karamunting (Rhodomyrtus tomentosa (Aiton) Hassk.) - Sagala , Vipi Zetiara; Ridwanto, Ridwanto; Daulay , Anny Sartika; Pulungan , Ainil Fithri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Karamunting leaves are a Myrtaceae family plant used as an antioxidant, antimicrobial, antiviral, anticancer, and antibacterial. This research aimed to determine secondary metabolite compounds, toxicity effects, and antibacterial activity in extracts and fractions of karamunting (Rhodomyrtus tomentosa (Aiton) Hassk.) leaves. This research includes characteristics, phytochemical screening, a BSLT (Brine Shrimp Lethality Test) method toxicity test, and an antibacterial test using the paper disc method. Toxicity tests were carried out with concentrations of (100, 200, 300, 400, 500, 600, 700, 800, 900, 1000) µg/mL, and antibacterial tests against staphylococcus aureus and Escherichia coli were carried out with concentrations of 10, 20 and 30%. The ethanol extract and ethyl acetate fraction results contain alkaloids, flavonoids, triterpenoids or steroids, tannins, and saponins. And the n-hexane fraction contains triterpenoids or steroids. Toxicity test of ethanol extract, n-hexane fraction, and ethyl acetate of karamunting leaves (Rhodomyrtus tomentosa (Aiton) Hassk.) has a toxic effect on Artemia Salina Leach. In the ethanol extract, an LC50 value of 92.593 µg/mL was obtained, followed by the n-hexane fraction with an LC50 value of 153.3829 µg/mL. Then, the ethyl acetate fraction LC50 value was 75.9328 µg/mL. LC50 value. Based on the results obtained from the ethanol extract, the n-hexane and ethyl acetate fractions of caramunting leaves (Rhodomyrtus tomentosa (Aiton) Hassk.) were classified in the toxic category, and the antibacterial test of the ethanol extract, the n-hexane and ethyl acetate fractions of caramunting leaves (Rhodomyrtus tomentosa (Aiton) Hassk.) has antibacterial activity against Staphylococcus aureus and Escherichia coli bacteria. The most potent inhibitory power was found in the ethyl acetate fraction with a concentration of 30% against staphylococcus aureus 16.1 mm and Escherichia coli 17.1 mm in the strong category.